Investment certificates under German taxation: Benefit or burden for structured products' performance? - Peter Scholz; Ursula Walther (Frankfurt School of Finance & Management, Centre for Practical Quantitative Finance (CPQF), 2010)
Despite their impressive market success, investment certificates' benefits are puzzling from both a theoretical and an empirical viewpoint. Previous research analyzed portfoliotheoretical issues, mispricing patterns, and counterparty risk. This work highlights the impact of taxation, which has not been previously addressed for these instruments. In order to capture tax effects, we simulate the entire return distributions of several structured products under the two most recent German taxation systems. Evaluation is done based on the concepts of stochastic dominance as well as expected utility. For the latter, we use both a risk neutral and a loss averse value function. Individual preferences prove relevant especially for those instruments that have been tailored to loss averse investors. We find significant tax effects, but they depend on the particular tax regime and the structure of the instrument. Interestingly, the introduction of the final withholding tax system substantially diminishes previously existing tax advantages.
Keywords: G11; 330; Abgeltungsteuer; bootstrapping; capital gain tax; expected return; expected utility; financial instruments; flat tax; Halbeinkünfteverfahren; historical simulation; investment certificates; return shaping; risk-return profiles; stochastic dominance; structured products; taxation; Investmentfonds; Hybrides Finanzprodukt; Kapitalertragsteuer; Wertzuwachssteuer; Steuerbelastung; Rendite; Risiko; Deutschland